IMPROVING ENGLISH LEARNING OUTCOMES USING IMPLEMENTATION OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) MODEL - Riyan Maulana; Ulfah Irani Z; Sayed Rahmat Aulia (IAI Al-Mawaddah Warrahmah Kolaka, 2023)
The implementation of the Cooperative Integrated Reading and Composition learning model that is applied to teaching materials allows the realization of ideas from students regarding changes and efforts to improve continuously and in accordance with the circumstances and conditions of the community environment where the school is located. The purpose of this research is to improve learning outcomes Reading subject English through Cooperative Integrated Reading and Composition (CIRC). This research was conducted from June to August at SMAN 1 Indrapuri for the 2021/2022 academic year. The research subjects were students of class XI-IPA consists of 23 students. Data collection tools were in the form of test items and student activity instrument sheets. There are two types of data validation required in this study, namely primary data and secondary data. Primary data consists of observations of student activities, and secondary data consists of student learning outcomes obtained from learning achievement tests. Data analysis using percentage descriptive statistics method. Performance indicators are used to measure the success of each cycle in this study. The research procedure consisted of two cycles. Each cycle consists of planning, implementation, observation and reflection. The results showed that there was an increase in student learning completeness from 54.1% to 76.8%. Based on the percentage of the number of students who experienced learning mastery in cycle II about 100%, the average value was 76.08.